2013
DOI: 10.3947/ic.2013.45.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Fluad®-MF59®-Adjuvanted Influenza Vaccine in Older Adults

Abstract: Influenza directly or indirectly contributes to the four leading causes of global mortality, at rates that are highest in older adults. As the proportion of older adults in the Korean population is greater than in most other countries, influenza prevention is a greater public health priority in Korea than elsewhere. Conventional inactivated influenza vaccine (IIV) is less immunogenic and efficacious (-50%) in older than in young adults, but adjuvanting the vaccine with oil-in-water emulsion MF59® increases imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 62 publications
0
61
1
Order By: Relevance
“…Indeed, that study did not quantify the natural attack rate of IVA/IVB in the elderly, as two of the only three studies identified did not report data of interest, while the third reported a natural attack rate of zero. The paucity of studies identified is not surprising; indeed, randomized placebo‐controlled trials have been very uncommon (at least in recent years) in this population group for purely ethical reasons, in that annual influenza vaccination is recommended for the elderly . This is why epidemiological and surveillance evidence is of importance …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, that study did not quantify the natural attack rate of IVA/IVB in the elderly, as two of the only three studies identified did not report data of interest, while the third reported a natural attack rate of zero. The paucity of studies identified is not surprising; indeed, randomized placebo‐controlled trials have been very uncommon (at least in recent years) in this population group for purely ethical reasons, in that annual influenza vaccination is recommended for the elderly . This is why epidemiological and surveillance evidence is of importance …”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the use of adjuvants in influenza vaccines has been limited, with only the MF59-adjuvanted trivalent seasonal vaccine licensed, and alum not widely investigated [35]. This is despite the use of aluminum salt adjuvants in vaccines since the 1920s, their status as the only licensed adjuvants in the USA until 2005, and the reduced effectiveness of unadjuvanted seasonal influenza vaccines in vulnerable populations such as the elderly [36,37].…”
Section: Adjuvantmentioning
confidence: 99%
“…CpG ODN was recently approved as a hepatitis B virus vaccine adjuvant. Addavax is a squalene‐based adjuvant similar to MF59, which is FDA‐approved and licensed in Europe for a seasonal influenza vaccine for elderly people . Here, we report that vaccinating Apoe ‐deficient ( Apoe −/− ) mice with ApoB P6 in Addavax was as atheroprotective as P6 in CFA/IFA.…”
Section: Introductionmentioning
confidence: 89%